Seasonal variations in the gut microbiota of white-headed black langur (Trachypithecus leucocephalus) in a limestone forest in Southwest Guangxi, China - Chen, Yanqiong; Lai, Ying; Zheng, Jingjin; Liu, Zheng; Nong, Dengpan; Liang, Jipeng; Li, Youbang; Huang, Zhonghao (Frontiers in Ecology and Evolution, 2023)
Investigating gut microbiota is important for understanding the physiological adaptation of animals to food availability changes in fragmented habitats and consequently providing new ideas for the conservation of endangered wild animals. In this study, we explored the gut microbiota of the endangered white-headed black langur (Trachypithecus leucocephalus), which is endemic to the limestone forests of Southwest Guangxi, China, to understand its adaptation strategies to seasonal changes in habitat using 16S rRNA sequencing. Our results revealed significant seasonal variations in the gut microbiota of white-headed black langurs. In particular, the alpha diversity was higher in the rainy season than in the dry season, and the beta diversity was significantly different between the two seasons. At the phylum level, the relative abundance of Firmicutes, Actinobacteriota, and Proteobacteria was higher in the dry season than that in the rainy season, whereas that of Bacteroidetes, Spirochaetota, and Cyanobacteria was significantly higher in the rainy season than that in the dry season. At the family level, Oscillospiraceae and Eggerthellaceae were more abundant in the dry season than in the rainy season, whereas Lachnospiraceae, Ruminococcaceae, and Monoglobaceae were more abundant in the rainy season than in the dry season. These results could have been obtained due to seasonal changes in the diet of langurs in response to food plant phenology. In addition, the neutral community model revealed that the gut microbiota assembly of these langurs was dominated by deterministic processes and was more significantly affected by ecological factors in the dry season than in the rainy season, which could be linked to the higher dependence of these langurs on mature leaves in the dry season. We concluded that the seasonal variations in the gut microbiota of white-headed black langurs occurred in response to food plant phenology in their habitat, highlighting the importance of microbiota in responding to fluctuating ecological factors and adapting to seasonal dietary changes.